Cellular Immune Responses in Islet Xenograft Rejection - Hu, Min; Hawthorne, Wayne J.; Yi, Shounan; O’Connell, Philip J. (Frontiers in Immunology, 2022)
Porcine islets surviving the acute injury caused by humoral rejection and IBMIR will be subjected to cellular xenograft rejection, which is predominately mediated by CD4+ T cells and is characterised by significant infiltration of macrophages, B cells and T cells (CD4+ and CD8+). Overall, the response is different compared to the alloimmune response and more difficult to suppress. Activation of CD4+ T cells is both by direct and indirect antigen presentation. After activation they recruit macrophages and direct B cell responses. Although they are less important than CD4+ T cells in islet xenograft rejection, macrophages are believed to be a major effector cell in this response. Rodent studies have shown that xenoantigen-primed and CD4+ T cell-activated macrophages were capable of recognition and rejection of pancreatic islet xenografts, and they destroyed a graft via the secretion of various proinflammatory mediators, including TNF-α, reactive oxygen and nitrogen species, and complement factors. B cells are an important mediator of islet xenograft rejection via xenoantigen presentation, priming effector T cells and producing xenospecific antibodies. Depletion and/or inhibition of B cells combined with suppressing T cells has been suggested as a promising strategy for induction of xeno-donor-specific T- and B-cell tolerance in islet xenotransplantation. Thus, strategies that expand the influence of regulatory T cells and inhibit and/or reduce macrophage and B cell responses are required for use in combination with clinical applicable immunosuppressive agents to achieve effective suppression of the T cell-initiated xenograft response.